Physical and mechanical properties of wood flour- recycle polypropylene composites under various wood flour sizes and modifier contents - Febrianto, Fauzi; Setyawati, Dina; Karina, Myrtha; Bakar, Edi Suhaimi; Hadi, Yusuf Sudo (2005)
The objective of this research was to evaluate the physical and mechanical properties of composites of wood flour (WF) and recycle polypropylene (RPP) prepared under various WF sizes and various maleic anhydride (MAH) modifier contents. The WF – RPP composites composed of 50% WF from Eucalyptus deglupta Blume species, 50% RPP, various sizes of WF (60~80; 80~100; and < 120 mesh), various contents MAH modifier (0, 1, 2.5, 5, 7.5, and 10%), and 15% dicumyl peroxide (DCP) initiator (based on MAH weight). Kneading conditions were set at 170°C, 10~50 rpm for 15 min. WF size and modifier content greatly affected the physical and mechanical properties of resulted composites. The smaller the WF size resulted in the greater the tensile strength of composites. Addition of MAH modifier improved the physical and mechanical properties of composites. WF-RPP composites with 120 mesh WF size and 2.5% MA modifier had tensile strength, breaking elongation and Young’s modulus about 2.15, 2.27, and 1.18 times, respectively higher compared with composites free-MAH modifier and absorbed considerably less water. Scanning electron microscope (SEM) indicated that addition of MAH improved the adhesion between WF and RPP.